Clinical impact of pulmonary hypertension on the outcomes of acute myocardial infarction patients with or without chronic obstructive pulmonary disease. Issue 3 (21st January 2022) - Oh, Seok; Kim, Ju Han; Cho, Kyung Hoon; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Ahn, Youngkeun; Jeong, Myung Ho
Abstract : Abstract: Acute myocardial infarction (AMI) and chronic obstructive pulmonary disease (COPD) are leading global causes of morbidity and mortality. In patients with both of these conditions, the presence of pulmonary hypertension (PH) can further worsen their prognosis. We examined the outcomes of AMI patients with COPD (AMI+COPD) and without COPD (AMI−COPD), depending on the presence or absence of PH. A total of 318 AMI patients with COPD (AMI+COPD cohort) (n = 109) or without COPD (AMI-COPD cohort) (n = 209) were included in this study and were subdivided into 2 groups according to right ventricular systolic pressure (RVSP) level (PH group [RVSP ≥35 mm Hg] and no PH group [RVSP <35 mm Hg]). We investigated characteristics and clinical outcomes in both the AMI-COPD and AMI+COPD cohorts. When investigating in-hospital clinical outcomes, the PH group had a higher proportion of new-onset heart failure (HF) in both cohorts. In the AMI+COPD cohort, however, the PH group had a higher incidence of cardiogenic shock than the no PH group, which was consistent with the result of the post-inverse probability of treatment weighting (IPTW) analysis. When investigating 1-year clinical outcomes, the PH group had higher incidences of a major adverse cardiac event and all-cause mortality in both cohorts. This finding was mainly driven by cardiac death in the AMI-COPD cohort, whereas it was mainly driven by non-cardiac death in the AMI+COPD cohort. After IPTW adjustment, these differences were statistically attenuated such that all variables were similar between both groups. PH may be associated with the development of new-onset HF (in all patients) and cardiogenic shock (in the AMI+COPD cohort). In addition, PH may be also associated with all-cause mortality, although it was statistically attenuated after IPTW adjustment. Abstract : Supplemental Digital Content is available in the text